The use of quantitative methods in a few case studies in the Indian context - Chaudhry, Amitav (Journal of Modern Languages, 2017)
The paper looks at the use of quantitative methods by the author and other quantitative linguists in the Indian multilingual context in a few domains of linguistics like text analysis, parameters of vocabulary balance, measuring language distance using the Mahalanobis D, stylistics, quantification in language attitudinal studies and the measurement of bilingualism.